Predictors of hemorrhagic complications after intravenous thrombolysis in acute cerebral infarction patients: A single-center study of 391 cases. Issue 37 (17th September 2021) - Zeng, Jianqi; Chen, Feng; Chen, Yiqian; Peng, Muli; Chen, Xingyu; Yang, Qingwei; Wang, Ru; Miao, Jiayin
Abstract : Abstract: For patients with ischemic stroke, intravenous (IV) thrombolysis with Urokinase within 6 hours has been accepted as beneficial, but its application is limited by high risk of hemorrhagic complications after thrombolysis. This study aimed to analyze the risk factors of hemorrhagic complications after intravenous thrombolysis using Urokinase in acute cerebral infarction (ACI) patients. Total 391 consecutive ACI patients were enrolled and divided into 2 groups: the hemorrhagic complications group and the non-hemorrhagic complications group. The related data were collected and analyzed. Univariate analysis showed significant differences in prothrombin time, atrial fibrillation (AF), Mean platelet volume, large platelet ratio (L-PLR), triglyceride (TG), Lactate dehydrogenase, alanine aminotransferase (ALT), high-density lipoprotein, and baseline National Institute of Health Stroke Scale score between the hemorrhagic complications and the non-hemorrhagic complications group ( P < .1). Multivariate logistic regression analysis indicated that AF (odds ratio [OR] = 2.91, 95% confidence interval [CI] = 1.06–7.99 P = .039) was the risk factor of hemorrhagic complications, while ALT (OR = 0.27, 95% CI = 0.10–0.72 P = .009) and TG (OR = 0.16, 95% CI = 0.06–0.45 P = .000) were protective factors of hemorrhagic complications. For patients with AF and lower levels of ALT or TG, the risk of hemorrhagic complications might increase after ACI.